2013
DOI: 10.5935/abc.20130109
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Left Atrial Volume and Diastolic Dysfunction in 500 Brazilian Patients

Abstract: BackgroundLeft atrial volume index (LAVI) increase has been associated to left ventricle (LV) diastolic dysfunction (DD), a marker of cardiovascular events (atrial fibrillation, stroke, heart failure, death). ObjectiveTo evaluate the relationship between LAVI and diferente grades od DD in Brazilian patients submitted to echocardiogram, studying LAVI increase determinants in this sample. MethodsWe have selected 500 outpatients submitted to echocardiography, after excluding arrhythmia, valvar or congenital cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 15 publications
8
36
1
Order By: Relevance
“…Besides, the elevated LV filling pressure in AF patients, which was estimated by E/e', was also found to be independently associated with atrial remodeling [33]. Therefore, the elevation of LV filling pressure was a good explanation for the increase in LA dimension and volume after LAAC in this study [34][35][36]. Further analysis with multivariable regression showed that the change of LV filling pressure in LAAC group, represented by the E/e' ratio, was independently associated with LVPWd (β = -2.23, p < 0.01, R = 0.477) (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Besides, the elevated LV filling pressure in AF patients, which was estimated by E/e', was also found to be independently associated with atrial remodeling [33]. Therefore, the elevation of LV filling pressure was a good explanation for the increase in LA dimension and volume after LAAC in this study [34][35][36]. Further analysis with multivariable regression showed that the change of LV filling pressure in LAAC group, represented by the E/e' ratio, was independently associated with LVPWd (β = -2.23, p < 0.01, R = 0.477) (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…In a greater cohort study – PREVEND - an analysis has been made for the causes of HFpEF occurring within the period of 11 years, the investigation showed that the advanced age, urinary albumin excretion, cystatin C and a history of atrial fibrillation were strongly indicated by occurrence of HFpEF. In the past two decades, the percent of the patients with preserved ejection fraction increased from 38% to 54% of all the cases with hearth failure and this percent was considered to increase progressively with aging of the population and with the increase of the prevalence of patients with hypertension, obesity and diabetes [ 2 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…LC is disturbed by diseases which disturb the energetic metabolism of calcium re-uptake such as myocardial ischemia and myocardial hypertrophy [ 6 ]. Aging, on its own, is directly connected with cardiac contractile dysfunction, which is manifested with prolonged time duration of the left chamber relaxation and stress intolerance [ 9 ]. It is proved, in trials, that aging, on its own, leads to diastolic dysfunction, oxidative stress and protein modification [ 9 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Nowadays, the term "diastolic dysfunction" is in use. Diastole is disturbed also in systolic HF and considered to be more stressing with further worsening of exercise intolerance and determines the prognosis and systolic contraction disturbances, so HF is a common entity with both phenotypes [4,5] The signs of myocardial DD are detected in people with almost any heart disease. Thus, in patients with arterial hypertension (AH), left ventricular diastolic dysfunction (LVDD) occurs in 50-90 % of cases and closely correlates with the degree of increase in blood pressure (BP) and AH presence.…”
Section: Historical Evolution Of Hf and Lvdd Evaluationmentioning
confidence: 99%